Implementation of Moringa Leaf Brownies Innovation as an Effort to Support Breast Milk Production and Prevent Stunting in Toddlers - Widya Ramadhini; Nurul Jannah (Sean Institute, 2026)
Moringa leaves (Moringa oleifera) are a local food source rich in nutrients such as protein, iron, calcium, and vitamins that are beneficial for breastfeeding mothers and toddlers. Moringa leaves are known to help support breast milk production and fulfill nutritional needs in efforts to prevent stunting. However, their utilization in the community is still limited to vegetable preparations, making it necessary to develop more attractive and easily consumable food innovations. This activity was carried out through several stages, including socialization, preparation of ingredients, production of moringa leaf brownies, packaging, and distribution to the community. In addition to product distribution, educational sessions were also conducted regarding the benefits of moringa leaves for breast milk production and stunting prevention in toddlers. Moringa leaf brownies were developed as a functional food with high nutritional value and greater community acceptance compared to conventional moringa leaf preparations. The results of the activity showed that moringa leaf brownies were well accepted by the community and have the potential to become an alternative local food product to help increase breast milk production in breastfeeding mothers and support the nutritional needs of toddlers in efforts to prevent stunting.